The Role of Entrepreneurship Education and Digital Literacy in Enhancing Innovation Through Motivation as an Intervening Variable - Muhammad Akbar Wiguna; Osly Usman (Journal of Digital Business and Global Economy, 2026)
The shift towards a digitally driven economy has transformed the way new ventures emerge and prompted universities to incorporate digital skills into their curriculum to prepare students for innovation. In this context the research focuses on the positive roles of entrepreneurship education and digital literacy in terms of innovation, as well as on the potential role of motivation as a mediatorship. Exploratory quantitative research approach was used; Data was collected using a 26 item questionnaire scored on a 5 point likert scale. The samples used was purposive with 50 students of Master of Management at Jakarta State University as the respondents. Partial Least Squares Structural Equation Modeling (PLS SEM) of the SmartPLS software was used in processing the responses. The results indicate that digital literacy has a positive and significant effect on motivation (β = 0.291) and innovation (β = 0.442), while motivation also has a positive and significant effect on innovation (β = 0.501). In contrast, entrepreneurship education had a positive but insignificant effect on motivation (β = 0.387) and a small, insignificant negative effect on innovation (β = −0.100). Mediation testing revealed that motivation partially mediated the effect of digital literacy on innovation, but did not mediate the effect of entrepreneurship education on innovation. While the sample size was limited, the results suggest that digital literacy, rather than theory based entrepreneurship education, was the stronger driving force behind innovation in this reinforcing group, exerting its influence both independently and by reinforcing motivation.